On the theory of decentralization, forests and livelihoods - Tacconi, L.; Siagian, Y.; Syam, R. (Australian National University, 2006)
The current theory and narrative states that democratic decentralization of forest management leads to sustainable forest management and improved livelihoods. Three assumptions underlie this theory and narrative: i) democratic decentralization is a means of institutionalizing and scaling up community-based natural resource management; ii) rural people benefit from the forest and will conserve it; iii) the success of decentralization can be measured by lack (or lower rates) of deforestation. The paper argues that the first two assumptions do not hold when tested with primary and secondary data and that the third assumption is incorrect and should be discarded. A revised theory of decentralized forest management needs to be developed and an initial sketch is discussed.